A study on effect of innovation and branding on performance of small and medium enterprises - Beitollah Akbari Moghaddam; Padide Armat (Management Science Letters, 2015)
TMarketing capabilities such as advertising and distribution, in the past, were considered as an intermediate level marketing activities but our focus in this study is on higher potentials of marketing, innovation and branding. The primary objective of this study is to investigate the effect of marketing capabilities on the market of small and medium enterprises in the province of Isfahan, Iran. The research consisted of small and medium enterprises in the industrial towns of the province of Esfahan using random sampling technique to gather the necessary data. Out of the 62 industrial parks and industrial zones in the province, there were 4,326 industrial units, which were active and the study distributes 384 questionnaires and managed to collect 308 properly filled ones. Using some statistical tests, the study has confirmed that innovation and branding influence positively on SMEs in this province.